Diversity Of Gastropod Types In The Intertidal Zone Of Kolbano Beach South Central Timor Regency, East Nusa Tenggara - Ndukang, Sardina; Missa, Hildegradis; Djalo, Aloysius (BIOEDUKASI, 2024)
Research on gastropods on Kolbano beach, South Central Timor Regency has never been published. The aim of this research was to determine the types of gastropods in the Intertidal Zone of Kolbano Beach, South Central Timor Regency. The samples used in the research were all gastropods located in plots located in the intertidal zone of Kolbano Beach. This research uses a qualitative approach, collecting research data using identification and documentation tables. Data analysis is completed using the Shanon Wienner Diversity Index formula. The results of the research showed that the gastropods successfully identified on Kolbano beach consisted of the species C.maldivus, B). C.flvidus, C). C.clerii, D). V. turbinllus, E). O. floralia, F). F. palidus, G). A.punctulata, H). Murex Blainvilli, I). Crassispira harpularia, J). T. reticulata, K). Plesiotrochus monachus, L). Persicula variabilis, M). C.scabridum, N). Vaceuelus favosus, O). Polinices tumidus, P). C.olidium, Q). M. moneta, R). Trochus maculates. S). Carolliophila solutistoma, T). M. myosotis. The results of the calculation of the diversity index, uniformity index and dominance index reached 2.195, so it can be concluded that the gastropods on Kolbano Beach consist of 16 families, 18 genera and 20 species and are at a medium level of diversity.